PENGARUH TEKANAN ANGGARAN WAKTU, TIPE KEPRIBADIAN AUDITOR, INDEPENDENSI KOMPETENSI AUDITOR TERHADAP KUALITAS AUDIT - Ausella Jean Fonda; Rahardja Rahardja (Diponegoro Journal of Accounting, 2014)
In the era of globalization today, the demands of society towards a quality auditor has increased over time. Auditors must consider time budget in various decision making. In addition, experience, auditor personality type, independence and competence can also improve competencies in decision making. The aim of this research is to test the influence of time budget pressure, auditor personality type, independence and competence the auditors against the quality of an audit. The population of this research are all an auditor who work in the office of the public accountant in the city of Semarang.Sampling method used is convenience sampling. The Data used in this research is the primary data, that is done using the method ofsurvey with questionnaire. Processing method used is regression analysis. The results showed that the auditor personality type, independence and competence of Auditors significant and positive impact on the quality of audits.